2012
DOI: 10.1016/j.cct.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Attrition and adherence of young women to aerobic exercise: Lessons from the WISER study

Abstract: The purpose of this report is to identify factors associated with attrition and adherence of young women to a 16-week randomized aerobic exercise intervention on biomarkers associated with breast cancer risk. The exercise group was prescribed a progressive weight-bearing aerobic exercise program consisting of 30 minute workouts, 5 times/wk for 16 weeks. Adherence was calculated as the average minutes of exercise per week during participation in the study. Of the total of 212 women randomized into the exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
3
18
1
1
Order By: Relevance
“…(Linke, Gallo, & Norman, 2011; Moroshko, Brennan, & O'Brien, 2011; Neve, Collins, & Morgan, 2010; Peels et al, 2012) Nonetheless, future physical activity interventions should make every effort to retain participants with, for example, a higher BMI at baseline, by including strategies/messages that directly address issues important to this subgroup (i.e., being physically active is important regardless of how much you weigh or whether you are trying to lose weight or not). Also, lower retention rates for ethnic minorities in randomized clinical trials are a concern;(Arikawa, O'Dougherty, Kaufman, Schmitz, & Kurzer, 2012; Moroshko et al, 2011; Murphy & Williams, 2013; Osann et al, 2011) however, we used several strategies that have been shown to maximize retention in clinical trials (i.e., establishing rapport, participants’ perception of the study as informative, etc. )(Barnett, Aquilar, Brittner, & Bonuck, 2012; D.…”
Section: Discussionmentioning
confidence: 99%
“…(Linke, Gallo, & Norman, 2011; Moroshko, Brennan, & O'Brien, 2011; Neve, Collins, & Morgan, 2010; Peels et al, 2012) Nonetheless, future physical activity interventions should make every effort to retain participants with, for example, a higher BMI at baseline, by including strategies/messages that directly address issues important to this subgroup (i.e., being physically active is important regardless of how much you weigh or whether you are trying to lose weight or not). Also, lower retention rates for ethnic minorities in randomized clinical trials are a concern;(Arikawa, O'Dougherty, Kaufman, Schmitz, & Kurzer, 2012; Moroshko et al, 2011; Murphy & Williams, 2013; Osann et al, 2011) however, we used several strategies that have been shown to maximize retention in clinical trials (i.e., establishing rapport, participants’ perception of the study as informative, etc. )(Barnett, Aquilar, Brittner, & Bonuck, 2012; D.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the duration and intensity of the exercise training in this study was not sufficient to alter SNS activity and thus change melatonin levels. Strengths of this trial include excellent adherence to the exercise treatment (7), large sample size, and selecting an exercise intervention based on current public health guidelines (8). …”
Section: Discussionmentioning
confidence: 99%
“…In our study, all exercise participants who completed follow up measurements had adherence levels of 80% or above, as calculated by the average minutes of exercise that participants reported as having completed per week for each of the four stages of exercise intensity. Analysis of study adherence and withdrawal was the subject of a separate examination (Arikawa et al, 2012). Most research has shown an inverse relationship between depressive symptoms and physical activity (e.g., Dunn 2005), as well as between perceived stress and physical activity (Aldana, 1996).…”
Section: Discussionmentioning
confidence: 99%